2008
DOI: 10.1016/j.jcme.2007.10.004
|View full text |Cite
|
Sign up to set email alerts
|

A feasibility study assessing manual therapies to different regions of the spine for patients with subacute or chronic neck pain

Abstract: Objective: The purpose of this project was to develop and test protocols for a randomized clinical trial of a combined therapeutic approach (thoracic spine and sacroiliac joint highvelocity, low-amplitude spinal manipulation [HVLA SM] + cervical spine postisometric relaxation) and cervical spine HVLA SM for patients with subacute or chronic neck pain. Methods: Patients were recruited in the Quad Cities in Iowa and Illinois. After a baseline assessment visit, eligible patients were randomly assigned to cervical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 14 publications
0
22
1
Order By: Relevance
“…2. With the exception of the observational studies, there were 2 randomized controlled trials 28,46 that reported on harms within their abstract. Three papers (from 76 studies) noted harms in the introduction of their paper.…”
Section: Clarifying Adverse Responses In Orthopaedic Physical Therapymentioning
confidence: 99%
See 3 more Smart Citations
“…2. With the exception of the observational studies, there were 2 randomized controlled trials 28,46 that reported on harms within their abstract. Three papers (from 76 studies) noted harms in the introduction of their paper.…”
Section: Clarifying Adverse Responses In Orthopaedic Physical Therapymentioning
confidence: 99%
“…Three papers (from 76 studies) noted harms in the introduction of their paper. 28,32,46 3. Only 5 of 76 studies 16,28,31,32,46 explicitly reported in their methods their intention to collect adverse event data.…”
Section: Clarifying Adverse Responses In Orthopaedic Physical Therapymentioning
confidence: 99%
See 2 more Smart Citations
“…6,7 Besides being effective in cervical pain complaints, vertebral repositioning is are also indicated in cases of radiculopathy. 1,[8][9][10][11][12][13] One of the manual therapy technique which promotes the mobilization of nerve roots and acts to test and treat the peripheral nervous system, is the neurodynamic mobilization. 14,15 The neural tissue has been pointed as a source radicular symptoms.…”
Section: Introductionmentioning
confidence: 99%